The people's act of love - Meek, James, 1962- (New York : Canongate, 2005)
In a remote Siberian town torn apart by civil war and inhabited by a small Christian sect, Anna Petrovna, a beautiful photographer, becomes involved in the fate of Samarin, an escapee from Russia's northernmost prison camp.
Keywords: Historical fiction; Christianity -- Fiction; Shamans -- Fiction; Siberia (Russia) -- Fiction; Historical fiction